2019
DOI: 10.1101/627265
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Population receptive field and connectivity properties of the early visual cortex in human albinism

Abstract: In albinism, the pathological decussation of the temporal retinal afferents at the optic chiasm leads to superimposed representations of opposing hemifields in the visual cortex. Here, we assessed the equivalence of the two representations and the cortico-cortical connectivity of the early visual areas.Applying fMRI-based population receptive field (pRF)-mapping (both hemifield and bilateral mapping) and connective field (CF)-modeling, we investigated the early visual cortex in 6 albinotic participants and 4 c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In patients with macular degeneration, Haak et al showed preserved corticocortical organization, when visually stimulated, between input-deprived portions of V1 > V2/V3 [24]. In early blind and anophthalmia cases, Bock et al found an intact corticocortical organization between V1 > V2/V3, even despite a complete absence of visual experience and retinal input [25]. Recently, Ahmadi et al [26] showed changes in corticocortical connections for V1 > V3 in albinotic participants.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with macular degeneration, Haak et al showed preserved corticocortical organization, when visually stimulated, between input-deprived portions of V1 > V2/V3 [24]. In early blind and anophthalmia cases, Bock et al found an intact corticocortical organization between V1 > V2/V3, even despite a complete absence of visual experience and retinal input [25]. Recently, Ahmadi et al [26] showed changes in corticocortical connections for V1 > V3 in albinotic participants.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we examined the BOLD contrast response characteristics of aberrant voxels in human albinism which respond to both the contra-and ipsilateral visual hemifields in the contralateral eye. Previous studies have shown that retinocortical miswiring in albinism results in partial cortical superposition of opposite hemifield representations in visual cortex such that single imaging voxels in these aberrant zones have two visual pRFs positioned roughly at mirror image locations across the vertical meridian (Ahmadi et al, 2019;Carvalho et al, 2020;Duwell et al, 2021;Hoffmann et al, 2003). However, while the opposite hemifield representation topographies are clearly superimposed at the macroscopic level and within individual voxels in albinism, it was still unclear whether the two conflicting hemifield inputs interact in any way.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of these aberrant hemifield overlap zones varies across individual subjects with albinism depending on the severity of miswiring (Hoffmann et al, 2003). Individual fMRI voxels within the aberrant zones were demonstrated to have bilateral, dual pRFs positioned at roughly mirror image locations across the vertical meridian (Ahmadi, Herbik, Wagner, Kanowski, Thieme, & Hoffmann, 2019;Carvalho, Invernizzi, Ahmadi, Hoffmann, Renken, & Cornelissen, 2020;Duwell, Woertz, Mathis, Carroll, & DeYoe, 2021). However, the cellular and columnar organization of these aberrant cortical zones is still not known in human albinism, and it is unclear whether the opposing hemifield inputs interact in any way.…”
Section: Introductionmentioning
confidence: 99%
“…The estimation of pRF properties, the delineation of the visual areas, and the visualization on the smoothed mesh surface were performed using Vistasoft, as described in (Ahmadi, Fracasso, et al 2019;Ahmadi, Herbik, et al 2019) . Polar angle and eccentricity maps were extracted and the misrouting extent was measured by calculating the mean eccentricity value [in degrees of visual angle] for the abnormal representation in a ROI drawn at the fundus of the calcarine sulcus that coincided with the representation of the horizontal meridian.…”
Section: Fmri Data Analysismentioning
confidence: 99%